Розробка модуля «аналіз результатів проведення виставок» іс «online галерея» - Старченко, Д. В. (ХНУРЕ, 2023)
The article describes the methods of analysis used for the online gallery`s improvement and competitiveness. There are defined the necessity of module development and the main goal is to monitor and analyze visitor behavior, sales, and exhibition performance in order to improve the exhibition campaign. The main characteristics are described and advantages of the methods for analysis in the article. The methods are Predictive Analysis, Visitor Segmentation Analysis, and Conversion Analysis. They work out the most important aspects of the exhibition results